(untitled) (Journal of history-rus, 2022)
The article is devoted to the review and methodological problems of preparing a consolidated catalog of cartographic materials on the history of Kazakhstan of the XVII – early XX centuries. Despite the importance and prospects of creating consolidated catalogs, at present there are no generalizing methodological solutions in this direction of the development of cartographic research and there is no software package that meets all the requirements for the design of a consolidated catalog of cartographic materials. The consolidated catalog of cartographic materials stands out among other types of catalogs by the complexity of the structure of construction and content. This undoubtedly leads to long-term design and various problems in its preparation. This circumstance directed the study towards the development of an interdisciplinary methodology for researching the consolidated catalog, which makes it possible to efficiently process and prepare «old» maps for the consolidated catalog of cartographic materials of the XVII – early XX centuries in the period of information technology. The article shows the main achievements, ways of solving methodological problems in the preparation of a consolidated catalog, consisting of 282 cartographic sources of high scientific and social significance, identified in the archives and libraries of Moscow and Orenburg during an interim study. The functionality of the developed consolidated catalog of «old» maps has been substantiated. The consolidated catalog of cartographic materials can be viewed as a kind of «guide» with the help of which the user can get answers to the following questions: in which of the archives, libraries and museum – there is the cartographic material necessary for the user (by title, chronology and territory); How does the administrative-territorial division change over time; The history of the location of socio-economic facilities in Kazakhstan of the XVII – early XX centuries. The consolidated catalog of cartographic materials can be used by scientists of the humanities and interdisciplinary areas in applied and scientific research, as well as by the general population in order to study the history of Kazakhstan in modern times. Key words: problems, methodology, consolidated catalog, cartographic materials of the XVII – early XX centuries.